Digital Transformation in BIPA Learning: Increasing Accessibility and Effectiveness Through Technology - Nasrullah, Riki; Prayogi, Arditya; Jannah, Rayhanun (LITERATUR : Jurnal Bahasa dan Sastra, 2024)
This research aims to understand how digital technology has changed how we learn Indonesian as a foreign language (BIPA). Through an in-depth review of various previous studies, it was found that digital technologies such as e-learning platforms, language applications, virtual reality (VR), and augmented reality (AR) have made a significant contribution to BIPA learning. E-learning platforms such as Moodle and Google Classroom make it easy to access learning materials anytime and anywhere, increasing learning flexibility. Language apps like Duolingo and Babbel, which are integrated with social media, create a more interactive and engaging learning environment. VR and AR technologies take the learning experience to a new level by allowing students to interact with language in a more realistic context.